The Reality of Teaching Methods Used in Humanities Education at the Faculty of Education – Traghen, University of Fezzan: A Perspective of Humanities Students (Sebha University Conference Proceedings, 2025)
This study aimed to identify the teaching methods used in the instruction of humanities at the Faculty of Education – Traghen, University of Fezzan, from the perspective of students in the Department of Humanities. It also sought to examine whether students’ views varied according to certain variables, namely their academic specialization and semester.The study adopted a descriptive approach, and data were collected through a questionnaire consisting of six dimensions, each addressing a specific teaching method: lecture, discussion, inquiry-based learning, cooperative learning, problem-solving, and individualized learning. The questionnaire was administered to a sample of 64 female students from the Department of Humanities.The study revealed the following findings:• The most commonly used teaching methods, as perceived by the students, were ranked as follows: inquiry-based learning, problem-solving, individualized learning, cooperative learning, lecture, and finally, discussion.• There were statistically significant differences in students’ perspectives based on their specialization (Arabic Language and Quranic Studies vs. Educational and Psychological Sciences and Sociology).• Statistically significant differences were also found based on academic semester (first to fourth vs. fifth to eighth).The study concluded with several recommendations, including:• Encouraging faculty members to adopt modern teaching methods through the organization of specialized training programs.• Raising faculty awareness about the importance of diversifying teaching strategies during lectures and promoting positive attitudes towards their use.